Expert Views on HPV Infection - Alison A. McBride (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Human papillomavirus (HPV) infections cause approximately 5% of all human cancers. While there are efficacious prophylactic vaccines that prevent infections with the most common cancer-associated HPVs, these vaccines are not widely available in low-resource settings and in many countries, including the US, HPV vaccination rates have remained disappointingly low. Moreover, vaccination does not modify existing HPV infections and the incidence of HPV-associated anal and oropharyngeal cancers has steadily increased and is projected to overtake the caseload of cervical cancer in the next two years. Hence, infections with cancer-associated HPVs will remain a major cause of morbidity and mortality, worldwide. This book provides state-of-the-art summaries and expert viewpoints on unresolved, controversial or emerging topics related to the natural history, evolution, biology, and disease association of papillomavirus infection. The individual chapters cover a wide range of thought provoking topics.